Autophagy, TGF-β, and SMAD-2/3 Signaling Regulates Interferon-β Response in Respiratory Syncytial Virus Infected Macrophages - Pokharel, Swechha M.; Shil, Niraj K.; Bose, Santanu (Frontiers in Cellular and Infection Microbiology, 2016)
Human respiratory syncytial virus (RSV) is a lung tropic virus causing severe airway diseases including bronchiolitis and pneumonia among infants, children and immuno-compromised individuals. RSV triggers transforming growth factor-beta(TGF-beta) production from lung epithelial cells and TGF-beta facilitates RSV infection of these cells. However, it is still unknown whether RSV infected myeloid cells like macrophages produce TGF-beta and the role of TGF-beta if any during RSV infection of these cells. Our study revealed that RSV infected macrophages produce TGF-beta and as a consequence these cells activate TGF-beta dependent SMAD-2/3 signaling pathway. Further mechanistic studies illustrated a role of autophagy in triggering TGF-beta production from RSV infected macrophages. In an effort to elucidate the role of TGF-beta and SMAD-2/3 signaling during RSV infection, we surprisingly unfolded the requirement of TGF-beta---SMAD2/3 signaling in conferring optimal innate immune antiviral response during RSV infection of macrophages. Type-I interferon (e.g. interferon-beta or IFN-beta) is a critical host factor regulating innate immune antiviral response during RSV infection. Our study revealed that loss of TGF-beta---SMAD2/3 signaling pathway in RSV infected macrophages led to diminished expression and production of IFN-beta. Inhibiting autophagy in RSV infected macrophages also resulted in reduced production of IFN-beta. Thus, our studies have unfolded the requirement of autophagy---TGF-beta---SMAD2/3 signaling network for optimal innate immune antiviral response during RSV infection of macrophages.